The INVESTIGATION OF GRAMMATICAL ERROR IN STUDENT’S ENGLISH WRITING AT UIN RADEN INTAN LAMPUNG AS BASIS FOR LEARNING MATERIAL DEVELOPEMENT - Kholid, Mohammad Fikri Nugraha; Rozi, Muhammad; Kholid, Idham (LPPM STKIP PGRI Bandar Lampung, 2021)
This research aims to investigate students's grammatical errors (morphological and syntactical) on phrase and clause level in English essay of UIN Raden Intan Lampung students’ as the basis for future learning material developement. Qualitative approach is used in this research. Research method which is used is descriptive qualitative with content analysis technique. Research data are words and sentences with morphological and syntactical error. In this research, interactive data analysis is used. The steps of the data analysis are data reduction, data display, and conclusion as well as verification. Validity of the data is done by using source triangulation. Based on the analysis and discussion result, there are several findings. The first is 3 types of morphological errors. They are noun, verb, and adjactive errors. The second is 5 syntactical errors. They are noun phrases (NP), verb phrases (VP), adverbial phrase (AvP, noun clause, and adjective clause errors. The third is the most dominant error (verb use error). There were 56 verb errors out of 107 total errors. Keywords: Grammatical error, morphology, syntax, qualitative research